Enhancing adolescent competence : strategies for classroom management - Miller, Darcy Elizabeth (Belmont, Calif. : Wadsworth, 1998)
Understanding classroom management. Understanding adolescence. Developing trust. Facilitating positive self-concepts. Improving motivation. Promoting self-determination. Building resiliency. Developing social skills. Responding to behavioral and emotional problems. Managing adolescents with mental illness.
Keywords: Classroom management; Teacher-student relationships; Adolescent psychology; Classroom management -- United States; Teacher-student relationships -- United States; Adolescent psychology -- United States